The big book of dyslexia activities for kids and teens 100 creative, fun, multi-sensory and inclusive ideas for successful learning - Reid, Gavin 1950-; Guise, Nick; Guise, Jennie (London Jessica Kingsley Publishers, 2018)
"Packed with fun, creative and multi-sensory activities, this resource will help children and teenagers with dyslexia become successful learners across the curriculum. The authors provide over one hundred tried-and-tested fun and imaginative activities and ideas to unlock the learning of children and teenagers with dyslexia in creative ways. The book is split into parts addressing literacy, numeracy, learning and cross curricular subjects. With fun activities like 'Spelling Ping-Pong' and 'Class Got Talent', it focuses on key skills such as listening, memory, spelling, writing and key board skills. Each activity includes a 'red herring' that will keep dyslexic children and teenagers entertained, extending them in interesting ways that will appeal to those who think outside of the box. Brimming with imaginative ideas, The Big Book of Dyslexia Activities is an essential toolkit for any teacher or parent working with children and young people with dyslexia" --Provided by publisher.
Literacy -- Reading -- Spelling -- Written expression -- Vocabulary expansion/grammar -- Learning -- General knowledge -- Comprehension -- Learning games for fun -- Memory : tricks and strategies -- Cross curricular -- Number work -- English as an additional language (EAL) -- Cross curricular -- Creativity and technology -- Home and school.
Age 7-16.
Keywords: Dyslexia -- Juvenile literature; Educational games -- Juvenile literature; Reading comprehension -- Juvenile literature